Roles of histone acetylation sites in cardiac hypertrophy and heart failure - Funamoto, Masafumi; Imanishi, Masaki; Tsuchiya, Koichiro; Ikeda, Yasumasa (Frontiers in Cardiovascular Medicine, 2023)
Heart failure results from various physiological and pathological stimuli that lead to cardiac hypertrophy. This pathological process is common in several cardiovascular diseases and ultimately leads to heart failure. The development of cardiac hypertrophy and heart failure involves reprogramming of gene expression, a process that is highly dependent on epigenetic regulation. Histone acetylation is dynamically regulated by cardiac stress. Histone acetyltransferases play an important role in epigenetic remodeling in cardiac hypertrophy and heart failure. The regulation of histone acetyltransferases serves as a bridge between signal transduction and downstream gene reprogramming. Investigating the changes in histone acetyltransferases and histone modification sites in cardiac hypertrophy and heart failure will provide new therapeutic strategies to treat these diseases. This review summarizes the association of histone acetylation sites and histone acetylases with cardiac hypertrophy and heart failure, with emphasis on histone acetylation sites.